Financial Counseling - Durband, Dorothy B.; Law, Ryan H.; Mazzolini, Angela K. (Springer International Publishing : Imprint: Springer, 2019)
"This text is a valuable new resource that we recommend for all of our professionals and are proud to incorporate as part of our AFC® certification program. With expertise representing the breadth and depth of the financial counseling profession, the content in this text provides you with a rigorous foundation of knowledge, considers critical theoretical models, and explores foundational skills of communication, self-awareness, and bias. This type of comprehensive approach aligns with our mission and vision-providing you with the foundational knowledge to meet clients where they are across the financial life-cycle and impact long-term financial capability." -Rebecca Wiggins, Executive Director, AFCPE® (Association for Financial Counseling and Planning Education®) This timely volume presents a comprehensive overview of financial counseling skills in accessible, practical detail for readers throughout the career span. Expert financial counselors, educators, and researchers refer to classic and current theories for up-to-date instruction on building long-term client competence, working with clients of diverse backgrounds, addressing problem financial behavior, and approaching sensitive topics. From these core components, readers have a choice of integrated frameworks for guiding clients in critical areas of financial decision-making. This essential work: · Offers an introduction to financial counseling as a practice and profession · Discusses the challenges of working in financial counseling · Explores the elements of the client/counselor relationship · Compares delivery systems and practice models · Features effective tools and resources used in financial counseling · Encourages counselor ethics, preparedness, and self-awareness A standout in professional development references, Financial Counseling equips students and new professionals to better understand this demanding field, and offers seasoned veterans a robust refresher course in current best practices.